A Review of Biogenic Volatile Organic Compounds from Plants: Research Progress and Future Prospects - Rongrong Luo; Xiaoxiu Lun; Rui Gao; Le Wang; Yuan Yang; Xingqian Su; Md Habibullah-Al-Mamun; Xiaohang Xu; Hong Li; Jinjuan Li (Toxics)
Biogenic volatile organic compounds (BVOCs) emitted by plants contribute to secondary air pollution through photochemical reactions in sunlight. Due to the influence of multiple factors, accurately characterizing and quantifying the emission of BVOCs from plant sources is challenging, which poses significant obstacles to the effective management and control of BVOCs. Therefore, this paper summarizes the emission mechanisms of BVOCs from plants, explores the primary factors influencing variations in the emission rates of these compounds, and evaluates the advantages and limitations of contemporary “measurement-modeling” methods for characterizing BVOC emissions. It is concluded that current measurement techniques still need to be further developed to meet the criteria of simplicity, affordability, and high precision simultaneously, and in terms of modeling and prediction studies, there is a lack of in-depth research on the atmospheric chemistry of BVOCs and the synergistic effects of multiple factors. Finally, it is suggested to leverage interdisciplinary strengths to develop advanced measurement technologies and high-resolution models for monitoring volatile compounds. Additionally, strategically selecting low-BVOC tree species in pollution-vulnerable urban areas—contingent on rigorous ecological assessments—combined with stringent controls on anthropogenic precursors (e.g., anthropogenic volatile organic compounds (AVOCs)) could serve as a complementary measure to mitigate secondary pollution.